The Role of Higher Institutions in Creating Awareness on Challenges of MUIP in Communicating its Waqf Possession - Noraini Mohamad; Zahanum Zulkifli (UIN Sunan Gunung Djati Bandung, 2015)
This paper analyzes the fenomena regarding issues of waqf and its impact on the ummah development. Waqf has significant impact on the ummah development in term of social, economic, political and legal process. The good governance of waqf institutions of waqf assets and properties, MUIP in particular has enhanced the economic, education and worship of the ummah within the MUIP jurisdiction. Waqf reported as an important aspect of religious ummah’s activity, that is increasing the awareness of social care.